Testing the Ability of Teachers and Students to Differentiate between Essays Generated by ChatGPT and High School Students - Tal Waltzer; Riley L. Cox; Gail D. Heyman (Human Behavior and Emerging Technologies)
The release of ChatGPT in late 2022 prompted widespread concern about the implications of artificial intelligence for academic integrity, but thus far there has been little direct empirical evidence to inform this debate. Participants (69 high school teachers, 140 high school students, total N=209) took an AI Identification Test in which they read pairs of essays—one written by a high school student and the other by ChatGPT—and guessed which was generated by the chatbot. Accuracy was only 70% for teachers, and it was slightly worse for students (62%). Self-reported confidence did not predict accuracy, nor did experience with ChatGPT or subject-matter expertise. Well-written student essays were especially hard to differentiate from the ChatGPT texts. In another set of measures, students reported greater optimism than their teachers did about the future role of ChatGPT in education. Students expressed disapproval of submitting ChatGPT-generated essays as one’s own but rated this and other possible academic integrity violations involving ChatGPT less negatively than teachers did. These results form an empirical basis for further work on the relationship between AI and academic integrity.